PERSPECTIVES ON GOVERNANCE NETWORKS RESEARCH ORIENTATIONS FOR ASSESSING COLLABORATIVE PUBLIC ADMINISTRATION - Meek, Jack (Revista Científica Foz, 2018)
This article offers three kinds of perspectives - or research orientations - for governance network: a system perspective, a participant perspective and a functional perspective. Each perspective drwas upon different kinds of assumptions (and units of analysis) for analysis - system benefits, inidividual benefits, network performance - in regard to the assessment of governance networks. The paper illustrates each of the approaches and concludes that all three perspectives can contribute to understanding and improving governance network contributions.